Population Origin and Heritable Effects Mediate Road Salt Toxicity and Thermal Stress - Conner, Lauren M.; Goedert, Debora; Fitzpatrick, Sarah W.; Fearnley, Amber; Gallagher, Emma L.; Peterman, Jessica D.; Forgione, Mia E.; Kokosinska, Sophia; Hamilton, Malik; Masala, Lydia A.; Merola, Neil; Rico, Hennesy; et al. (2023)
Human impacts on wild populations are numerous and extensive, degrading habitats and causing population declines across taxa. Though these impacts are often studied individually, wild populations typically face suites of stressors acting concomitantly, compromising the fitness of individuals and populations in ways poorly understood and not easily predicted by the effects of any single stressor. Developing understanding of the effects of multiple stressors and their potential interactions remains a critical challenge in environmental biology. Here, we focus on assessing the impacts of two prominent stressors affecting many organisms across the planet – elevated salinity (an increasingly common pollutant in freshwater habitats) and elevated temperature. We examined a suite of physiological traits and components of fitness across populations of wood frogs originating from ponds that differ in their proximity to roads and thus their legacy of exposure to road salt pollution. When experimentally exposed to road salt, wood frogs showed reduced survival, especially those from ponds adjacent to roads, and delayed time to metamorphosis. Family level effects mediated these outcomes, but high salinity generally eroded family level variance. When combined, exposure to both temperature and salt resulted in very low survival, and this effect was strongest in roadside populations. Taken together, these results suggest that temperature is an important stressor capable of exacerbating impacts from a prominent contaminant confronting many freshwater organisms in salinized habitats. More broadly, it appears likely that toxicity might often be underestimated in the absence of multi-stressor approaches.
Keywords: Climate change; Maladaptation; SCSU-student; amphibians; dept.bio; local adaptation; pollution; road salt